A Proposed Training Program to Enhance Administrative Competencies of Academic Administrators at the Jordanian Universities in Light of the Change Administration Requirements - Fatma Samih Mohammed Abo Alian; Khaled Ali Al Serhan (University of Science and Technology, Yemen, 2016)
Abstract:            Study aimed at constructing a proposed training program to enhance administrative competencies of academic administrators at the Jordanian universities in light of the change administration requirements. The study sample comprised  (621) academic administrators working at various Jordanian universities for the academic year )2013-2014( The inferential statistics such as mean, t-test, standard deviation, Scheffe test, Pearson correlation coefficient and One-Way Analysis of Variance ANOVA were used to analyze the data. The results indicated that the degree of applying change management policies by academic administrators was intermediate, and that the degree of administrative skills of university academic administrators was also intermediate. The researcher recommended a training program to be conducted in order to develop the administrative skills of academic administrators in various